Effects of kenaf contents and fiber orientation on physical, mechanical, and morphological properties of hybrid laminated composites for vehicle spall liners. Issue 8 (25th April 2014) - Yahaya, R.; Sapuan, S.M.; Jawaid, M.; Leman, Z.; Zainudin, E.S.
<x xml:space="preserve">Abstract</x> The aim of this work is to study the effect of kenaf volume content and fiber orientation on tensile and flexural properties of kenaf/Kevlar hybrid composites. Hybrid composites were prepared by laminating aramid fabric (Kevlar 29) with kenaf in three orientations (woven, 0o/90o cross ply uni‐directional (UD), and non‐woven mat) with different kenaf fiber loadings from 15 to 20% and total fiber loading (Kenaf and Kevlar) of 27–49%. The void content varies between 11.5–37.7% to laminate with UD and non‐woven mat, respectively. The void content in a woven kenaf structure is 16.2%. Tensile and flexural properties of kenaf/Kevlar hybrid composites were evaluated. Results indicate that UD kenaf fibers reinforced composites display better tensile and flexural properties as compared to woven and non‐woven mat reinforced hybrid composites. It is also noticed that increasing volume fraction of kenaf fiber in hybrid composites reduces tensile and flexural properties. Tensile fracture of hybrid composites was morphologically analysed by scanning electron microscopy (SEM). SEM micrographs of Kevlar composite failed in two major modes; fiber fracture by the typical splitting process along with, extensive longitudinal matrix and interfacial shear fracture. UD kenaf structure observed a good interlayer bonding and low matrix cracking/debonding. Damage in composite with woven kenaf shows weak kenaf‐matrix bonding. Composite with kenaf mat contains the high void in laminates and poor interfacial bonding. These results motivate us to further study the potential of using kenaf in woven and UD structure in hybrid composites to improve the ballistic application, for example, vehicle spall‐liner. POLYM. COMPOS., 36:1469–1476, 2015. © 2014 Society of Plastics Engineers